Pengaruh Green Product, Green Promotion, Dan Green Packaging Terhadap Loyalitas Konsumen Dengan Green Trust Sebagai Mediasi (Studi Pada Industri Green Fashion) - Zulvania Aulia Izzuhda; Agustina Fitrianingrum (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to analyze the influence of green products, green promotions, and green packaging on consumer loyalty with green trust as a mediating variable in the green fashion industry. The background of this study is the increasing consumer awareness of environmental issues, so that an effective and sustainable green marketing strategy is needed. The approach used is quantitative with a causal method and purposive sampling technique. The study population is Muslim consumers in Central Java province, especially those domiciled in Semarang City, Demak Regency, and Jepara Regency, who have purchased green fashion products from brands that apply green marketing principles. The sample was determined using the Lemeshow formula, with a minimum number of respondents required of 96 people, to support the PLS-SEM analysis. The research instrument was compiled based on the green marketing mix theory, trust theory and ethical values ​​in Islam. The proposed hypotheses include: (1) green product, green promotion, and green packaging influence green trust, (2) green trust influences consumer loyalty, (3) the combination of the three green marketing elements has a direct influence on consumer loyalty. This research is expected to provide a conceptual contribution to the development of green marketing models, as well as practical implications for fashion industry players in designing sustainable marketing strategies that build consumer loyalty.